ANALISIS EFEKTIVITAS SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) PEMERINTAH KABUPATEN GIANYAR - Agus Putrawan, Nyoman; Dwija Putri, I.G.A. Made Asri; Ariyanto, Dodik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study examines the effectiveness of technology-based information systems with using models DeLone and McLean (1992) and developed by Seddon and Kiew (1996). This study modifies model s Seddon and Kiew (1996) and applied to the public sector . The purpose of this study to test the effect of system quality, information quality, top management support on the usefulness and user satisfaction. Data were collected through a survey method with questionnaire technique. Respondents were taken using purposive sampling method with with individual analysis unit. Total respondents 108 user SIMDA applications in 36 units working. The study was conducted in October 2016 and the data analysis technique used is the partial least squares (PLS). Based on the results of empirical testing and discussion can be concluded that the quality of information and top management support positive effect on usefulness, but the quality of system has no effect on the usefulness. System quality, information quality, usefulness has positive effect on user satisfaction, but the top management support has not effect on user satisfaction.
Keywords: quality systems, quality information, top management support, usefulness, user satisfaction